2020
DOI: 10.1038/s41598-020-59476-4
|View full text |Cite
|
Sign up to set email alerts
|

An electronic alert system increases screening for hepatitis B and C and improves management of patients with haematological disorders

Abstract: treatment of haematological disorders in patients with chronic hepatitis B or resolved infection (anti-HBc-positive) is associated with a risk of hepatitis B reactivation. Moreover, patients with chronic hepatitis C have a higher risk of haematological malignancies than general population. An electronic alert system was developed to promote screening of hepatitis B (HBV) and c (HcV) in patients starting haematological therapies. The system included screening and linkage to care and a request for testing in tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“… 18 A recent study from Spain also reported significant increase in HBV and HCV screening rates from 60.5% to 87.8% in 420 hematology patients after electronic alert system. 20 Our alert system also significantly increased HBsAg (from 55.1% to 93.1%) and anti-HBc IgG screening rates (from 4.3% to 79.4%) in patients receiving IST. However, our system had several important advantages over the previously defined ones.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“… 18 A recent study from Spain also reported significant increase in HBV and HCV screening rates from 60.5% to 87.8% in 420 hematology patients after electronic alert system. 20 Our alert system also significantly increased HBsAg (from 55.1% to 93.1%) and anti-HBc IgG screening rates (from 4.3% to 79.4%) in patients receiving IST. However, our system had several important advantages over the previously defined ones.…”
Section: Discussionmentioning
confidence: 68%
“…Up to our knowledge, there are only a few studies about the use of electronic alert systems for increasing HBV screening rates before starting IST. 13 , 17 - 20 In a study from Spain, PRESCRIB project, an alert system increased HBsAg (from 47% to 94%) and anti-HBc IgG screening rates (from 29% to 85%) in patients receiving biologic agents. 17 In a Japanese study, HBView, an alert system increased anti-HBc IgG screening rates from 71% to 84% in patients receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We can also think that more awareness and education to clinicians about HBVr risk associated with chemotherapy could be necessary as many patients increased their hepatic enzymes during chemotherapy but the majority have not been tested for HBV. In other centers, strategies to promote and increase universal HBV screening and follow-up in cancer patients range from the use of computer alert programs [36][37][38][39] , electronic medical order check for anti-CD20 antibody treatment 40 or electronic alerts to monitor HBV-DNA every 3 months 41 . All those methods are considered imperfect and strategies need to be adapted to the local clinical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic reminder systems have been used for hepatitis screening for many years in many countries, including the United States, Japan, China, and Spain. The target populations for the implementation of the systems in clinical practice include baby boomers in the United States, for HCV screening, and patients with hematological disorders, outpatients, and inpatients at hospitals, for HBV and HCV screening [14][15][16]. In the United States, alert systems improved the screening rate from 10% to 64% [15].…”
Section: Discussionmentioning
confidence: 99%